Perspectives for integrating housing location considerations and transport planning as a means to face social exclusion in Indian cities - Geetam Tiwari (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This paper highlights the urban development in India and implications for low income households living in informal settlements or slums. The paper is divided into four sections. Section 1 describes urban development pattern in India. Section 2 presents a summary of policies since 1950 which have been implemented to address the housing needs of low income households in cities. Section 3 presents impacts of various housing and resettlement policies in selected cities in India. Section 4 summarizes key insights from self-planned low income settlements in cities-the slums, and expert planned low income settlements as part of resettlement policies.
Keywords: 330; Wohnstandort; Wohnungspolitik; Verkehrsplanung; Soziale Ausgrenzung; Stadt; Indien